Pá-Tiden. (Stockholm : Moderna museet, 1996)
Bachelder, Steven ; Capelán, Carlos ; Ellberg, Carin ; FA+ ; Hietala, Jan ; Isaeus-Berlin, Meta ; Johansson, Bengt Olof ; Johansson, Stefan ; Ketter, Clay ; Kristensson, Anders ; Lindberg, Maria ; Lundberg, Mikael ; Matz, Ebba ; Miesenberger, Maria ; Opitz, Stina ; Sense ; Sjöberg, Martin ; Svenungsson, Jan ; Thulin, Anne ; Tottie, Sophie ; Wolgers, Anna Tegeström
biografie, bibliografie
kunstcatalogus